WOMEN IN REPRODUCTIVE SCIENCE: Anti-Müllerian hormone: a look back and ahead. Issue 6 (December 2019) - Josso, Nathalie
Abstract : Anti-Müllerian hormone (AMH) is a member of the TGF-β family secreted by immature Sertoli cells and by granulosa cells of growing ovarian follicles. In males, it induces the regression of fetal Müllerian ducts and represses androgen synthesis through receptors located on the Leydig cell membrane. In female mice, AMH inhibits primary follicle recruitment and sensitivity to FSH. Measurement of circulating AMH is of value to pediatric endocrinologists allowing them to detect the presence and functional activity of testicular tissue without resorting to stimulation by human chorionic gonadotropin. In women, AMH levels are correlated with the size of the ovarian follicle pool and provide information on the likelihood of spontaneous or induced pregnancy.